Efficient Underwater Wireless Data Transmission Technique and Signal Processing - Dur-e-Jabeen; Habib Shaukat; Mehwish Siddiqui; Sarah Ahmed; Muhammad Yasir Zaheen; Amad Ud Din ahmad; Hassan Ali Mirza; Muhammad Sami (Engineering Proceedings, 2023)
This paper is based on a project titled underwater acoustic communication in which communication is performed between transmitter and receiver side underwater using water as a channel; data are is transmitted through a piezo transducer underwater, which are then be received by a receiver, i.e., a wireless hydrophone. Signal processing and analysis are performed on the received wireless signals. Data reception and propagation are important parts on the receiver side, which involve conditioning and processing of the received signal. Morse code is used to detect the signals and processed data, which are then analyzed using MATLAB simulation software.